THE ROLE OF THE PRINCIPAL’S VISIONARY LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATION: A LITERATURE REVIEW - Matdio Siahaan; Hasanuddin Hasanuddin; Tutiek Yoganingsih (Yayasan Education and Social Center, 2023)
The purpose of this activity is to reuse waste and reduce the accumulation of household waste so that floods do not occur and to use waste with the creations and innovations of the surrounding community. Apart from that, it is also to increase people's income by collecting and exchanging waste every week with garbage collectors or trading it with other used goods that are suitable for use at RW-03 Harapan Baru, Bekasi Utara. The type of research in this thesis is a qualitative descriptive research and taking primary data sources using purposive sampling technique. Data collection techniques are carried out in three ways, namely observation, interviews, and documentation. The data analysis technique used consisted of data reduction, data presentation and drawing conclusions. The results show that waste management provides many benefits to the surrounding community, the environment becomes comfortable, beautiful, green, and adds to the community's economic income. This activity received support from several parties such as the local government, the PKK driving team, and Care for the Environment, so that the skills of residents to process waste increase in quality and quantity. The conclusion from this study is that household waste can bring benefits from a social, economic and environmental perspective for the welfare of residents in RW.03 Harapan Baru Bekasi